Rosácea: puesta al día - Pezo C., Carlo; Soto P., Rosamary; Rosas Ch., Carlos; Fuenzalida B., Marcela; Lemus A., David (Revista Hospital Clínico Universidad de Chile, 2013)
Rosacea is a chronic inflammatory disease. Its frequency is higher in pale-skinned people and women over 30 years. Disease mechanisms include: abnormalities in innate immunity, inflammatory reactions to microorganisms, ultraviolet radiation damage, and vascular dysfunction. There are four clinical subtypes: erythematotelangiectatic, pustular papules, phymatous and ocular rosacea. Patients may present one or more characteristics of each subtypes. Injuries are classically located in midface area. Extreme temperatures, UV radiation, hot beberages, spicy foods, alcohol, exercise, topical irritants, psychological symptoms and drugs are associated to exacerbations. Clinical evaluation of the patient is usually enough for diagnosis. Nonpharmacologic interventions are essential for treatment. These include avoiding use of cosmetic, and triggers, skin care, and broad-spectrum sun protection. Patients with no response to general measures can respond to pharmacological agents. Topical metronidazole and azelaic acid are considered first-line treatments in mild to moderate disease. Oral tetracycline, have been used for many years for the treatment of papulopustular rosacea. Isotretinoin is useful in refractory disease. Treatment must be continous to maintain the response.